Deriving shallow‐water sediment properties using post‐stack acoustic impedance inversion. Issue 2 (18th December 2018) - Vardy, Mark E.
ABSTRACT: In contrast to the use of marine seismic reflection techniques for reservoir‐scale applications, where seismic inversion for quantitative sediment analysis is common, shallow‐waterm, very‐high‐resolution seismic reflection data are seldom used for more than qualitative reflection interpretation. Here, a quantitative analysis of very‐high‐resolution marine seismic reflection profiles from a shallow‐water (<50 m water depth) fjord in northern Norway is presented. Acquired using Sparker, Boomer, and Chirp sources, the failure plane of multiple local landslides correlates with a composite reflection that reverses polarity to the south. Using a genetic algorithm, a 1D post‐stack acoustic impedance inversion of all three profiles is performed, calibrating against multi‐sensor core logger (MSCL) data from cores. Using empirical relationships the resulting impedance profiles are related to remote sediment properties, including: P‐wave velocity; density; mean grain size; and porosity. The composite reflector is consistently identified by all three data sources as a finer‐grained (by one ϕ ), lower density (c. 0.2 g/cm 3 less than background) thin bed, with an anomalous low velocity zone (at least 100 m/s lower than background) associated with the polarity reversal to the south. Such a velocity contrast is consistent with an accumulation of shallow free gas trapped within the finer‐grain, less permeable layer. This study represents the first application of acoustic impedance inversion to very‐high‐resolution seismic reflection data and demonstrates the potential for directly relating seismic reflection data with sediment properties using a variety of commonly used shallow seismic profiling sources.